A validated multidisciplinary study on the assessment of SMS messages as a mean to improve self-efficacy in university students - Oliveira, Diana; Esgalhado, Graça; Oliveira, Daniel; Garcia, Nuno (Proceedings of the ... International Workshop on Education Technology and Computer Science, 2014)
This paper describes a multidisciplinary study that included teams from the Psychology and from the Computer Science departments on the use of interactive Short Message Service messages to assess psychological changes in self-efficacy of Engineering students exposed to motivational and persuasive texts. The paper presents the definition of the platform, the configuration and setting in place of the system that handled the exchange of automatic and interactive messages with the research subjects, as well as the implementation and results of the Psychology study. The assessment of the results of this experiment, also presented, were obtained by comparing scores of self-efficacy questionnaires given, pre and post study, to both an experimental and a control group.